Synthesis of 1,1-Bis-[2-Hydroxy-3-(1’-Benzoyl/Pyridoyl-5’-Aryl-Pyrazolin-3’-yl)-5-Methyl Phenyl] Methane - Kinhikar, R.V.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
New 1,1 bis-[2-hydroxy-3-(1'-benzoyl-5'-aryl-pyrazolin-3'-yl)- 5-methyl phenyl ] methane (6a-f) and 1,1-bis-[2-hydroxy-3-(1'pyridoyl- 5'-aryl-pyrazolin-3'-yl)-5-methyl phenyl ] methane (7a-f) have been synthesised by the action of 1,1-bis-[2-hydroxy-3-(3-arylprop- 2-en-1-one)-5-methyl phenyl ] methane (4a-f) with benzoic acid hydrazide and isoniazid respectively in pyridine medium.